Magnetic Resonance Imaging Combined with Serological Markers Improves the Diagnosis of Placenta Previa with Placenta Accreta Spectrum - Ying Wang; Zhengdong Hou; Bingqing Xia; Xianjing Xie; Ying He (Clinical and Experimental Obstetrics & Gynecology)
Background: Placenta previa (PP) combined with placenta accreta spectrum (PAS) is a serious obstetric condition that increases the risk of maternal and fetal complications. Early diagnosis is therefore crucial for improving outcomes. The aim of this study was to evaluate the accuracy of magnetic resonance imaging (MRI) combined with three serological markers (alpha-fetoprotein [AFP], creatine kinase [CK], and soluble fms-like tyrosine kinase-1 [sFlt-1]) for the diagnosis of PP with PAS. Methods: This retrospective study included 243 patients with suspected PP and PAS treated at two hospitals between August 2018 and August 2023. Patients were divided into two groups based on surgical and pathological findings: PP+PAS (+) and PP+PAS (–). The serum levels of AFP, CK, and sFlt-1 were measured, and optimal diagnostic thresholds were determined using receiver operating characteristic (ROC) curve analysis. The diagnostic performance of MRI, serological markers, and a combination of the two was compared with that of surgical pathology. Results: Serum AFP, CK, and sFlt-1 levels were significantly higher in the PP+PAS (+) group compared to the PP+PAS (–) group. The optimal thresholds of AFP, CK, and sFlt-1 for the diagnosis of PP+PAS (+) were 58.49 U/mL, 168.25 U/mL, and 2.28 ng/mL, respectively. A combined diagnostic approach using MRI and serological markers showed good accuracy, with a Kappa coefficient of 0.850, indicating good agreement with surgical pathology. Conclusions: Combining MRI with serological markers (AFP, CK, and sFlt-1) provides enhanced diagnostic accuracy for detecting PP with PAS as compared to either method alone. This approach can facilitate early diagnosis, improve clinical decision-making, and reduce the risks associated with surgical intervention.